The Canadian election studies : assessing four decades of influence - Bilodeau, Antoine, 1976-; Kanji, Mebs, 1969-; Scotto, Thomas J. (UBC Press, 2012)
A collection of essays examining the ongoing Canadian Election Studies (CES) project, whose primary objective has been to investigate why Canadians vote the way they do.